THE EFFECT OF THIRD PARTY FUNDS GROWTH, CREDIT GROWTH, NON PERFORMING LOAN (NPL) AND INTEREST RATE ON PROFITABILITY IN CONVENTIONAL COMMERCIAL BANKS LISTED ON IDX FOR THE PERIOD 2018-2021 - Haninah Haninah; Gregorius N.Masdjojo (Jurnal Ekonomi, 2022)
Profitability refers to the ability of a business to generate profits within a certain period of time by using productive assets or capital, such as total capital and own capital. However, poor profitability may imply that management's financial performance is less than desirable in terms of generating profits. To see an increase in profitability in a company, external and internal parties will pay attention to several factors that can affect profitability. This study was conducted to examine and analyze the effect of growth of third party funds, credit growth, non-performing loans (NPL) and interest rates on profitability. The population used in this study is conventional commercial bank companies listed on the Indonesia Stock Exchange for the 2018-2021 period. The sample used in this study were 129 companies using the purposive sample method. Data analysis technique using multiple linear regression analysis. The results of the analysis obtained in this study are the growth of third party data, credit growth and interest rates have a significant positive effect on profitability, while non-performing loans (NPL) have no effect on profitability.